Storage and fractions of soil organic matter under no‑tillage and conventional planting systems of cabbage - Melo, Gabriel Bressiani; Pereira, Marcos Gervasio; Perin, Adriano; Guareschi, Roni Fernandes; Soares, Paula Fernanda Chaves (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the humic, granulometric, and oxidizable fractions of soil organic matter, the light organic matter content in the soil, and C and N contents and storage in an Oxisol under no-tillage and conventional tillage systems for cabbage cultivation. Pasture areas and native cerrado soil were used as a control. The samples were collected in 2014 at the 0.0–0.05 and 0.05–0.10-m soil depths, after one cabbage crop cycle under no-tillage and conventional tillage systems, in an area with a long history of conventional tillage for vegetable crops. The no-tillage system increases the contents of light organic matter, C and N, as well as C storage and the values of particulate organic C, organic C associated with minerals, and the humic and oxidizable fractions of organic matter. The no-tillage system improves soil quality, in comparison with conventional tillage, besides providing, for most of the variables, higher values than those observed in the pasture area and similar values to those of the area under native cerrado.